2011
DOI: 10.1002/rcm.5069
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature reversed‐phase liquid chromatography coupled to isotope ratio mass spectrometry

Abstract: Compound-specific isotope analysis (CSIA) by liquid chromatography coupled to isotope ratio mass spectrometry (LC/IRMS) has until now been based on ion-exchange separation. In this work, high-temperature reversed-phase liquid chromatography was coupled to, and for the first time carefully evaluated for, isotope ratio mass spectrometry (HT-LC/IRMS) with four different stationary phases. Under isothermal and temperature gradient conditions, the column bleed of XBridge C(18) (up to 180 °C), Acquity C(18) (up to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 47 publications
1
46
0
Order By: Relevance
“…Barbituric acid, melamine and humic acid were analyzed as model compounds that are resistant to oxidation, and thus potentially affecting DOC and SI analyses . We found a recovery rate of ≥99%, proving complete oxidation.…”
Section: Resultsmentioning
confidence: 84%
“…Barbituric acid, melamine and humic acid were analyzed as model compounds that are resistant to oxidation, and thus potentially affecting DOC and SI analyses . We found a recovery rate of ≥99%, proving complete oxidation.…”
Section: Resultsmentioning
confidence: 84%
“…However, note that these highly oxidative conditions may significantly reduce the lifetime of the filament in the mass spectrometer. This problem can be reduced by using an oxygen scrubber online directly from the helium stream with the sample before it is introduced into the ion source of the mass spectrometer …”
Section: Methodsmentioning
confidence: 99%
“…This problem can be reduced by using an oxygen scrubber online directly from the helium stream with the sample before it is introduced into the ion source of the mass spectrometer. 13,23 For all analyses, the same concentrations of reagents were used:…”
Section: Analytical Setupmentioning
confidence: 99%
“…As a first example Godin et al used temperatures up to 170°C to separate hydrosoluble fatty acids and phenolic acids via a very hydrophobic porous graphitic carbon column [130]. Because commercially available columns often do not support these temperatures [130], Zhang et al investigated four different stationary phases and showed that under isothermal and temperature gradient conditions, column bleed had no effect on the precision and accuracy of d 13 C values [131]. These results are promising for compound-specific isotope analysis of polar organic contaminants by hightemperature LC-IRMS.…”
Section: Liquid Chromatography-irms (Lc-irms)mentioning
confidence: 97%